2022
DOI: 10.3390/ijms23105496
|View full text |Cite
|
Sign up to set email alerts
|

One of the Primary Functions of Tissue-Resident Pluripotent Pericytes Cells May Be to Regulate Normal Organ Growth and Maturation: Implications for Attempts to Repair Tissues Later in Life

Abstract: Adult mesenchymal stem cells were reported more than 30 years ago. Since then, their potential to repair and regenerate damaged or diseased tissues has been studied intensively in both preclinical models and human trials. Most of the need for such tissue repair/regeneration is in older populations, so much of the effort has been performed with autologous cells in older patients. However, success has been difficult to achieve. In the literature, it has been noted that such progenitor cells from younger individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 127 publications
(170 reference statements)
0
4
0
Order By: Relevance
“…Thus, some cells in the bone may play an amplification role regarding the influence of the neural input into the bone environment. Such cells could be the equivalent of the pluripotent regulatory cells that have been postulated to play a role in tissue regulation [ 45 ]. In microgravity, such a regulatory mechanism may be compromised, and exercise alone cannot overcome this deficit.…”
Section: Responses Of Humans To Space Flight and Living In Leomentioning
confidence: 99%
“…Thus, some cells in the bone may play an amplification role regarding the influence of the neural input into the bone environment. Such cells could be the equivalent of the pluripotent regulatory cells that have been postulated to play a role in tissue regulation [ 45 ]. In microgravity, such a regulatory mechanism may be compromised, and exercise alone cannot overcome this deficit.…”
Section: Responses Of Humans To Space Flight and Living In Leomentioning
confidence: 99%
“…The above discussion regarding NSC begs the question “are the findings with NSC unique to this population, or are they similar to experiences with other stem/progenitor cell populations to affect tissue repair and regeneration?” Based on the published literature, the effort with neural cells is likely not unique in that in some respects a similar path has been observed with MSC first reported by Caplan (reviewed in [ 15 , 16 , 17 , 18 ]). That is, the in vitro abilities of MSC from sources such as bone marrow, adipose tissue, or others to differentiate towards the chondrogenic, osteogenic, and adipogenic lineages by exposure to unique “cocktails” of growth factors, biochemical, media, and serum were seized upon by a myriad of researchers to exploit these abilities in vivo to effect repair and attempt to regenerate tissues such as cartilage, ligaments, tendons, and menisci that had been damaged by injury or disease [ 19 , 20 ]. However, analogous to the experience with neural “stem” cells, the in vivo experience with MSC was met with limited success after a significant investment and significant effort by researchers worldwide.…”
Section: Parallels Between Nsc and Mesenchymal Stem Cells/medicinal S...mentioning
confidence: 99%
“…Recently, it was suggested that perhaps a primary role for MSC was in the young rather than the elderly [ 19 ], and that MSC from older individuals were compromised due to epigenetic alterations induced during life experiences and other aging contributions. This perspective is supported by considerable literature on the subject [ 19 ], and thus, it is also likely that a similar construct holds for NSC as well as MSC (assuming they are different in some respects). Therefore, unless it is possible to “refresh” stem cells from older individuals, the construct of using autologous cells from elderly patients may not lead to the successful outcomes that are needed.…”
Section: Is There An Influence Of Age On the Success Of Nsc Implantat...mentioning
confidence: 99%
“…A common niche for mesenchymal progenitors is the perivascular space, and there is considerable evidence in the literature for regenerative potential of pericytes when applied to bone. Pericytes, characterized by high expression of neural/glial antigen 2 (NG2) and platelet-derived growth factor rector β (PDGFRβ), have been implicated in the repair and regeneration of tissues damaged by injury [ 23 ].…”
Section: Introductionmentioning
confidence: 99%